Bowhead Whale (Balaena mysticetus) Migration and Calling Behaviour in the Alaskan Beaufort Sea, Autumn 2001–04: An Acoustic Localization Study - Blackwell, Susanna B.; Richardson, W.J.; Greene, Jr., C.R.; Streever, B. (ARCTIC, 2009)
The westward migration of bowhead whales (Bering Sea stock) was studied during autumn 2001–04 as part of an oil industry monitoring program. An array of Directional Autonomous Seafloor Acoustic Recorders (DASARs) was deployed northeast of the Northstar oil production island near Prudhoe Bay, Alaska. Underwater sounds were recorded continuously for 24–35 days per year, mainly in September. More than 130 000 bowhead calls were detected, and the directional capability of DASARs allowed triangulation of whale position for ~93 500 calls. The migration pathway was closer to shore in 2003–04 than in 2001–02. Calls were clumped in space and time, and there was significantly more calling at night than by day. From 65% to 82% of calls were simple frequency-modulated calls, and the percentage of complex calls was positively related to the daily number of calls. No songs were detected, but in 2004 there were numerous call sequences consisting of repeated identical calls in series and generally lasting up to a few minutes. The DASAR methodology provides detailed information on the temporal and spatial distribution of calling whales and on their acoustic repertoire. La migration à l’ouest de la baleine boréale (population de la mer de Béring) a été étudiée durant quatre automnes (2001-2004) dans le cadre d’un programme d’étude de l’industrie pétrolière. Un réseau d’enregistreurs sous-marins autonomes et directionnels (DASAR) a été déployé au nord-est de Northstar, une île artificielle d’exploitation pétrolière près de Prudhoe Bay en Alaska. Des enregistrements sous-marins continus ont été récoltés pendant 24 à 35 jours chaque année, principalement pendant le mois de septembre. Plus de 130 000 appels de baleines ont été enregistrés et la capacité directionnelle des DASAR a permis de déterminer par triangulation la position des baleines pour ~ 93 500 de ces appels. Le corridor de migration s’est avéré plus proche de la côte en 2003-2004 qu’en 2001-2002. Les appels des baleines étaient groupés dans le temps et l’espace et il y ...